Harvest mortality in North American mallards: A reply to Sedinger and Herzog1. Issue 4 (4th March 2013) - Pöysä, Hannu; Dessborn, Lisa; Elmberg, Johan; Gunnarsson, Gunnar; Nummi, Petri; Sjöberg, Kjell; Suhonen, Sari; Söderquist, Pär
Abstract Sedinger and Herzog (2012) evaluated the evidence for the impact harvest mortality may have on North American duck populations. While doing that, they questioned our review (Pöysä et al. 2004) and conclusion that harvest mortality in North American mallards (Anas platyrhynchos) may have shifted from compensatory to additive over the period from the 1960s to the 1980s. In this reply, we correct Sedinger and Herzog's misrepresentations of our 2004 paper and argue that our interpretations of the results published at that time have not been invalidated. © 2013 The Wildlife Society.